APOBEC2 safeguards skeletal muscle cell fate through binding chromatin and regulating transcription of non-muscle genes during myoblast differentiation - Lorenzo, Jose Paulo; Molla, Linda; Amro, Elias Moris; Ibarra, Ignacio L.; Ruf, Sandra; Neber, Cedrik; Gkougkousis, Christos; Ridani, Jana; Subramani, Poorani Ganesh; Boulais, Jonathan; Harjanto, Dewi; Vonica, Alin; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
The apolipoprotein B messenger RNA editing enzyme, catalytic polypeptide (APOBEC) family is composed of nucleic acid editors with roles ranging from antibody diversification to RNA editing. APOBEC2, a member of this family with an evolutionarily conserved nucleic acid-binding cytidine deaminase domain, has neither an established substrate nor function. Using a cellular model of muscle differentiation where APOBEC2 is inducibly expressed, we confirmed that APOBEC2 does not have the attributed molecular functions of the APOBEC family, such as RNA editing, DNA demethylation, and DNA mutation. Instead, we found that during muscle differentiation APOBEC2 occupied a specific motif within promoter regions; its removal from those regions resulted in transcriptional changes. Mechanistically, these changes reflect the direct interaction of APOBEC2 with histone deacetylase (HDAC) transcriptional corepressor complexes. We also found that APOBEC2 could bind DNA directly, in a sequence-specific fashion, suggesting that it functions as a recruiter of HDAC to specific genes whose promoters it occupies. These genes are normally suppressed during muscle cell differentiation, and their suppression may contribute to the safeguarding of muscle cell fate. Altogether, our results reveal a unique role for APOBEC2 within the APOBEC family.